Adaptability of some legume trees on quartz tailings of a former tin mining area in Bangka Island, Indonesia - B H Narendra; P Pratiwi (Brawijaya University, 2016)
Tin mining activities in Bangka Island, besides their important role in contributing to state revenues, also caused damage to the environment, among others in the form of quartz tailings overlay. To rehabilitate this land, in addition to the necessary efforts to improve soil conditions, success is also determined by the selection of appropriate plant species. This study was aimed to determine the adaptability of some legume trees grown on the quartz tailings in land rehabilitation trials in the post tin mining areas of Bangka Island. The legume trees tested were Calliandra calothyrsus Meisn., Caesalpinia sappan L., Enterolobium cyclocarpum (Jacq.) Griseb., Gliricidia sepium (Jacq.) Walp., Delonix regia ( Hook.) Raf., and Cassia siamea Lamk. Treatments of growing media applied in the field were medium I (a mixture of 20% organic material, 20% top soil, 1% NPK fertilizer, 5% calcium, and 54% quartz tailings), media II (a mixture of 25%organic material, 25%top soil, 2% NPK fertilizer, 6% calcium, 42% quartz tailings), and media III (a mixture of 30% organic material, 30% top soil, 3% NPK fertilizer, 7% calcium, and 30% quartz tailings). The observation was done by measuring the height and diameter of the stem of the plants, as well as the viability of one year after planting. Analysis of the results of measurements of stem height and diameter showed their diversity. Enterolobium cyclocarpum had the largest dimensions, while the lowest was Caesalpinia sappan. At the age of one year in the field, Gliricida sepium and Enterolobium cyclocarpum showed the average ability of the high life of up to 100%, whereas Calliandra calothyrsus was totally death. In general, the types of legumes selected in this trial showed good adaptability, except for of Calliandra calothyrsus